2018
DOI: 10.3389/fncel.2018.00048
|View full text |Cite
|
Sign up to set email alerts
|

Precision of Classification of Odorant Value by the Power of Olfactory Bulb Oscillations Is Altered by Optogenetic Silencing of Local Adrenergic Innervation

Abstract: Neuromodulators such as noradrenaline appear to play a crucial role in learning and memory. The goal of this study was to determine the role of norepinephrine in representation of odorant identity and value by olfactory bulb oscillations in an olfactory learning task. We wanted to determine whether the different bandwidths of olfactory bulb oscillations encode information involved in associating the odor with the value, and whether norepinephrine is involved in modulating this association. To this end mice exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…These studies combined with our findings suggest that GCs in the OB likely mediate the pattern separation in M/T cells. This hypothesis is further supported by a recent study showing that odor-induced changes in the power of local field potential oscillations in the OB also display learning-related separation (Ramirez-Gordillo et al, 2018). A previous study has shown that GC-specific silencing does not alter the firing rate of mitral cell (Fukunaga et al, 2014).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These studies combined with our findings suggest that GCs in the OB likely mediate the pattern separation in M/T cells. This hypothesis is further supported by a recent study showing that odor-induced changes in the power of local field potential oscillations in the OB also display learning-related separation (Ramirez-Gordillo et al, 2018). A previous study has shown that GC-specific silencing does not alter the firing rate of mitral cell (Fukunaga et al, 2014).…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have shown that both odor-induced oscillations in the OB and odor responses in M/T cells differ between FA and CR trials (Ramirez-Gordillo et al, 2018;Wang et al, 2019), which are incorrect and correct responses to the same odorant (S-), respectively. Using the methods described above, we analyzed GC activity during the Hit, FA, and CR trials in the last session of the go/no go task.…”
Section: Gcs Encode Odorant Valuementioning
confidence: 99%
“…Both the number of units responding to odours and the number of units showing divergent response to S+ (rewarded odour) and S− (unrewarded odour) increases, after the animals learned to discriminate odours (Figure ), suggesting strong plasticity of M/Ts responding to odours during learning . Similar plasticity has been also found for oscillations of local field potentials in behaving rodents . Furthermore, whether this type of plasticity exists in the olfactory sensory neurons is controversial .…”
Section: Neural Representation Of Odour Under Different States: Anaesmentioning
confidence: 69%
“…Although specific manipulation of noradrenergic neurons by optogenetics is feasible, surprisingly only 1 study has used this technique to date. This study finds that Optogenetic inhibition of adrenergic fibres alters odorant‐induced changes in power of oscillations in the OB in mice learning to discriminate odorants . Information is still lacking about the effects of optogenetic activation of noradrenergic inputs on odour‐related spiking in the OB in awake animals.…”
Section: Feedback and Centrifugal Modulation Of The Obmentioning
confidence: 87%
See 1 more Smart Citation